Immunity to viruses: learning from successful human vaccines - Pulendran, Bali (2013)
For more than a century immunologists and vaccinologists have existed in parallel universes. Immunologists have for long reveled in using “model antigens,” such as chicken egg ovalbumin or nitrophenyl haptens to study immune responses in model organisms such as mice. Such studies have yielded many seminal insights about the mechanisms of immune regulation, but their relevance to humans has been questioned. In another universe, vaccinologists have relied on human clinical trials to assess vaccine efficacy, but have done little to take advantage of such trials for studying the nature of immune responses to vaccination. The human model provides a nexus between these two universes, and recent studies have begun to use this model to study the molecular profile of innate and adaptive responses to vaccination. Such “systems vaccinology” studies are beginning to provide mechanistic insights about innate and adaptive immunity in humans. Here we present an overview of such studies, with particular examples from studies with the yellow fever and the seasonal influenza vaccines. Vaccination with the yellow fever vaccine causes a systemic acute viral infection and thus provides an attractive model to study innate and adaptive responses to a primary viral challenge. Vaccination with the live attenuated influenza vaccine causes a localized acute viral infection in mucosal tissues, and induces a recall response since most vaccinees have had prior exposure to influenza, and thus provides a unique opportunity to study innate and antigen-specific memory responses in mucosal tissues and in the blood. Vaccination with the inactivated influenza vaccine offers a model to study immune responses to an inactivated immunogen. Studies with these and other vaccines are beginning to reunite the estranged fields of immunology and vaccinology, and yielding unexpected insights about mechanisms of viral immunity. Therefore, vaccines that have been proven to be of immense benefit in saving lives offer us a new fringe benefit: lessons in viral immunology.